Augmented cerebellar lactate in copper deficient rat pups originates from both blood and cerebellum - Gybina, Anna A. (2009)
Copper (Cu) is essential for proper brain development, particularly the cerebellum, and functions as a cofactor for enzymes including mitochondrial cytochrome c oxidase (CCO). Cu deficiency severely limits CCO activity. Augmented lactate in brain of Cu deficient (Cu−) humans and cerebella of Cu− rats is though to originate from impaired mitochondria. However, brain lactate may also originate from elevated blood lactate. The hypothesis that cerebellar lactate originates from elevated blood lactate in Cu− rat pups was tested. Analysis of Cu− and Cu adequate (Cu+) rat pups (experiment I) revealed blood lactate was elevated in Cu− rat pups and cerebellar lactate levels were closely correlated to blood lactate concentration. A second rat experiment (experiment II) assessed Cu− cerebellar lactate without the confounding factor of elevated blood lactate. Blood lactate levels of Cu− rat pups in experiment II were equal to those of controls; however, Cu− cerebellar lactate was still elevated, suggesting mitochondrial impairment by Cu deficiency. Treatment of rat pups with dichloroacetate (DCA), an activator of mitochondrial pyruvate dehydrogenase complex (PDC), lowered Cu− cerebellar lactate to control levels suggesting PDC inhibition is a site of mitochondrial impairment in Cu− cerebella. Results suggest Cu− cerebellar lactate originates from blood and cerebellum.